Microwave-Assisted Synthesis and Characterization of Iron Oxide Nanoparticles for Advanced Biomedical Sensing Applications - Vivek Pratap Singh; Chandra Prakash Singh; Santosh Kumar; Saurabh Kumar Pandey; Deepak Punetha (IEEE Open Journal of Nanotechnology)
This study focuses on the synthesis and characterization of Superparamagnetic Iron Oxide Nanoparticles (IONPs) with potential biomedical and sensing applications. These nanoparticles are in high demand for their biocompatibility, biodegradability, and superparamagnetic properties. In contrast to traditional high-temperature synthesis methods, microwave-assisted co-precipitation provides notable benefits, such as improved superparamagnetic characteristics, a high surface-to-volume ratio, large surface area, and simplified separation processes. The synthesis process utilized microwave-assisted co-precipitation, and a range of characterization techniques, including XRD, FESEM, VSM, FTIR, and UV-spectroscopy, were employed to assess the properties of the iron oxide nanoparticles. Analysis of the XRD, FTIR, and UV-spectroscopy results confirmed the formation of IONPs, predominantly comprising magnetite (Fe3O4). The microwave-synthesized IONPs exhibited superparamagnetic behavior, featuring an average crystallite size of 9 nm and robust saturation magnetization values (up to 68 emu/g). These attributes render them highly suitable for applications such as MRI contrast agents, thermal mediators in hyperthermia, drug delivery systems, and advanced sensor technologies, including magnetic sensing and biosensing applications, where their high magnetic responsiveness and surface functionalization capabilities can be effectively leveraged.